Compliance or Culture Shift: Reflecting on the Impact of Education Inspection on Educational Institutions - Joana, Luciana; de Carvalho, Maria João (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2024)
This reflective work delves into education inspection as an entity operating across various countries. It draws from international organizations, particularly the OECD, for operational guidelines and support to ensure the quality and evaluation of educational services, and is seen as pivotal in evaluating and monitoring educational institutions in many countries. Inspectors gauge education quality and hold schools accountable for achieving teaching, organizational, and leadership objectives. Despite recognizing the diversity of educational systems and governmental mechanisms from a European standpoint, their actions have both positive outcomes. These comprise organizational improvement through fostering self-evaluation and guiding organizational changes, and unintended negative consequences, including minimal impacts on student progress and increased workload for educators, highlighting the complex nature of inspection systems. Inspection systems exert pressure on schools, fostering intentional consequences and serving as benchmarks for improvement. It can be concluded that globalization drives convergence in methodologies and shapes educational policies across nations.